Realizacija predlogov razvrščanja prizadetih otrok v obdobju 1963-1981 - Štrukl-Kurilo, Ana; Topolovec, Darinka (Obzornik zdravstvene nege, 1984)
The Mental Hygiene Unit of Ljubljana-Centre Chi1dren 's Outpatient Clinic offers health services to pre-school children and provides diagnostic management and treatment for children with mental retardation of various levels. The work of the Unit encompasses also parental and community counseling. The Unit is staffed by a professional team filling also afunction of a first-degree commission for evaluation and classification of children with retarded mental and physical development. During the period 1963-1981, 610 retarded children were submitted to such evaluation. Through questionnaries given to parents of 591 children attending the Unit, the professional team was provided information about their further accomplishmens, as well as about actual application of the proposed classification to the management of these children.